Pengaruh Kualitas Produk, Citra Merek Dan Harga Terhadap Keputusan Pembelian Produk Kosmetik Wardah ( Studi Pada Mahasiswa Umsida Pengguna Kosmetik Wardah ) - Rahayu, Ajeng; Febriansah, Rizky Eka; Yulianto, Moch Rizal (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to determine the purchasing decisions for Wardah cosmetic products through product quality. Brand image, and Price. This research is descriptive and uses a quantitative approach. The sample was taken using the Non Probability Sampling technique with the Purposive Sampling method, involving a total of 100 respondents. Data was collected through the distribution of questionnaires. Data analysis was conducted using mulriple linear regression analysis with the statistical tool SPSS version 25. The results of this study indicate that product quality affects purchasing decisions for Wardah cosmetic products, bramd image affects purchasing decisions for Wardah cosmetic products, and price affects purchasing decisions for Wardah cosmetic products.